Influencia del uso de la amilasa, invertasa y xilanasa en la fermentación de la industria panificadora. - Aviléz Chica, Anahís Yamileth (2024)
The case study addresses the deficiencies presented by the process of the application of enzymes such as amylase, invertase and xylanase in the various products that are made in the baking industry, in addition, The baking industry is a crucial sector within what is the food field, this industry deploys a wide variety of products that satisfy the tastes of the consumer around the world. Therefore, the importance of correct handling and application of these enzymes in the fermentation process is highlighted, also emphasizing the need for adequate technical training, as well as compliance with food safety regulations, to have an adequate use, therefore, it requires a greater understanding and proper application of enzymes in baking. so that it can improve the quality of the dough and the competitiveness of bakeries. The activity of amylase is essential for the quality, texture and preservation of the final product, The controlled application of invertase instead improves fermentation, taste, texture and above all shelf life, therefore, xylanase in fermentation can improve the extensibility of the dough and above all result in a more uniform crumb and improved texture. The correct application of these enzymes gives numerous benefits, which include improved texture, longer shelf life of the product, and above all a significant reduction in waste.